Exposure to Violence, Trauma, and Juvenile Court Involvement: A Longitudinal Analysis of Mobile Youth and Poverty Study Data, Mobile, Alabama, 1998-2011 - Bolland, Anneliese ([Verlag nicht ermittelbar], 2020)
This project consists of secondary analysis material (syntax only, no data). The original study that the material pertains to is an examination of predominantly African American adolescents who live in extreme poverty. The study suggested that exposure to violence is positively related to involvement in the juvenile court system, and partially mediated by psychological factors, particularly hopelessness; thus, practitioners should take care to target more than just traumatic stress as a result of exposure to violence in African American impoverished youth.